Time remaining:
12. Please express Y as a function of X by rewriting the equation. Thanks!

Algebra
Tutor: None Selected Time limit: 0 Hours

Apr 27th, 2015

ln y = ln x + ln(x + 17) + ln C

we know  ln(a*b)= ln(a) + ln(b) 

so ln y = ln(x(x+17)) + ln C = ln(x²+17x) + ln C  =  ln (C(x²+17x)) = ln(Cx² + 17Cx) 

and we know  : ln(a) = ln(b) => a=b

so  :  y = Cx² + 17Cx

Good luck please if you don't understanding something tell me 

Apr 26th, 2015

Did you know? You can earn $20 for every friend you invite to Studypool!
Click here to
Refer a Friend
...
Apr 27th, 2015
...
Apr 27th, 2015
Mar 22nd, 2017
check_circle
Mark as Final Answer
check_circle
Unmark as Final Answer
check_circle
Final Answer

Secure Information

Content will be erased after question is completed.

check_circle
Final Answer